Effects of habitat fragmentation on the population genetic diversity of the Amur minnow (Phoxinus lagowskii) - Xue, Zhuang (Mitochondrial DNA B Resour, 2017)
Phoxinus lagowskii is a freshwater fish that is widely distributed in China. In this study, a comparative analysis of the mtDNA control region (D-loop) was performed to analyze the natural population structure and genetic diversity of 54 individuals from eleven locations (T1, T2, T3, T4, T5, T6, T7, T8, T9, T10 and T11) which was divided with reservoirs. The estimated haplotype and nucleotide diversity were 0.734 and 0.03514, respectively. An AMOVA indicated that 79.78% of the total variation originated from individual populations and 20.22% came from variation within the 11 geographic populations, which showed high genetic differentiation among the 11 geographic groups. A test of neutral evolution and mismatch distribution indicated that historical expansion occurred in these populations. However, the findings of low genetic diversity and high genetic differentiation demonstrated that the reproduction isolated by reservoir has showed a certain effect for the development of the populations, and the results should provide new information for the conservation and exploitation of this species.